How does fuel taxation impact new car purchases? An evaluation using French consumer-level data - Pauline Givord; Céline Grislain-Letrémy; Helene Naegele (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This study evaluates the impact of fuel prices on new car purchases, using exhaustive individual-level data of monthly registration of new private cars in France from 2003 to 2007. Detailed information on the car holder enables us to account for heterogeneous preferences across purchasers. We identify demand parameters through the large oil price fluctuations of this period. We find that the sensitivity of short-term demand with respect to fuel prices is generally low. Using these estimates, we assess the impact of a policy equalizing diesel and gasoline taxes. Such a policy would reduce the share of diesel in new cars purchases from 69% to 66% in the short-run, without substantially changing the average fuel consumption or CO2 emission levels of new cars. Alternatively, a carbon tax would slightly decrease the CO2 emission levels of new cars in the short-run (by 0.1%) without any significant impact on the share of diesel cars purchased.
Keywords: C25; D12; H23; L62; Q53; 330; fuel prices; automobiles; carbon dioxide emissions; environmental tax